Factors that affect post-graduation satisfaction of Chilean university students. Issue 6 (3rd June 2019) - Espinoza, Oscar; González, Luis Eduardo; McGinn, Noel; Castillo, Dante; Sandoval, Luis
ABSTRACT: Universities' reputations are built in part on graduates' assessments of the quality of education they received. What do these assessments tell us? Are graduates' judgments of quality based on their experiences as students or on their later job satisfaction, that is, on process or on outcomes? The objective of this study was to assess the extent to which Chilean university graduates' satisfaction with their professional training is associated with experiences during the degree program they pursued, employment experiences including salary level, or the prestige level or image of the university they attended. Survey questionnaires were used to collect data from recent graduates of professional programs in Primary-Secondary Teaching and Psychology in three universities that differ in prestige. A linear regression model shows that graduates' satisfaction with their degree program is a joint function of family background, program quality and university image, but not salary once graduated.